2020
DOI: 10.1099/jmm.0.001256
|View full text |Cite
|
Sign up to set email alerts
|

Comparing DADA2 and OTU clustering approaches in studying the bacterial communities of atopic dermatitis

Abstract: Introduction. The pathogenesis of atopic dermatitis (AD) is not yet fully understood, but the bacterial composition of AD patients’ skin has been shown to have an increased abundance of Staphylococcus aureus . More recently, coagulase-negative Staphylococcus (CoNS) species were shown to be able to inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…At each sampling time point, the stratum corneum was collected using a tape-stripping technique ( 22 , 39 ). Five consecutive adhesive, d -Squame tapes (22 mm diameter; CuDerm, Dallas TX, USA) were placed onto the skin and pressed for 10 s with standardized pressure (225 g/cm 2 , d -Squame Pressure Instrument D500).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At each sampling time point, the stratum corneum was collected using a tape-stripping technique ( 22 , 39 ). Five consecutive adhesive, d -Squame tapes (22 mm diameter; CuDerm, Dallas TX, USA) were placed onto the skin and pressed for 10 s with standardized pressure (225 g/cm 2 , d -Squame Pressure Instrument D500).…”
Section: Methodsmentioning
confidence: 99%
“…Tapes underwent DNA extraction using a DNeasy blood and tissue kit (Qiagen, Germany) per the manufacturer’s instructions, with a few modifications as previously outlined ( 39 ). Similarly, metabarcoding was performed targeting the universal V3-V4 16S rRNA region of bacteria using the 341F (5′- CCTAYGGGRBGCASCAG -3′) and 806R (5′- GGACTACNNGGGTATCTAAT -3′) primers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…used Paired-end assembler for Illumina sequences (PANDAseq) for read assembly and Quantitative Insights into Microbial Ecoloby (QIIME) for quality control and analysis, whereas here a pipeline that combines several other publicly available tools was used (Illumina-utils, USEARCH, and QIIME, among others; see Data S1 ). This moderate pipeline-based variation in results is expected ( O'Rourke et al., 2020 ; Bokulich et al., 2018 ; Xue et al., 2018 ; Rajan et al., 2019 ; Barnes et al., 2020 ). Despite these discrepancies in the abundances of select taxa, we emphasize that our re-analysis identified the same suite of dominant taxa in the marmoset microbiome that were originally described by Kap et al., with Actinobacteria , Firmicutes and Bacteroidetes present at high (>10%) relative abundances.…”
Section: The Microbiome In Healthy Marmosets and How It Compares To Humansmentioning
confidence: 75%
“…Since the release of PURC, several studies have demonstrated shortcomings of OTU clustering, which is the method PURC used to infer biological sequences. In particular, OTU clustering tends to overestimate the number of sequences, is sometime unreproducible (repeat runs yield different OTUs), and it is difficult to determine appropriate similarity thresholds (Callahan et al, 2017;Barnes et al, 2020;Joos et al, 2020;Nelson et al, 2020), with the overestimation problem reported for PURC specifically (Morales-Briones and Tank, 2019;Blischak et al, 2018). An alternative approach to identify and separate PCR and sequencing errors from biological sequences is to apply an error model, where read abundance, composition, and quality scores are used to infer whether each unique read is likely to have been derived from another observed sequence (Callahan et al, 2016).…”
Section: Purc V20mentioning
confidence: 99%